Peranan Alat Deteksi Kebakaran Dalam Menunjang Keselamatan di Kapal MT. Mabrouk - Erwin Sutantyo; Susanti Susanti (Jurnal Maritim Polimarin, 2022)
One of the efforts to prevent or reduce accidents at work is the use of work safety tools. Fires can occur anywhere, one of which can occur in water transportation equipment, namely ships. Ship accidents caused by fire hazards are very likely to occur. Ships must be detected early to prevent the occurrence of such fires. Therefore, it is necessary to know the use of fire detection equipment in supporting safety on ships. The aim is to prevent fire hazards from spreading and support the ship’s safety, cargo, and, humans. life. This research was carried out on the ship MT Mabrouk. The method used in this research /is a qualitative method that produces descriptive data. Based on the results of research and discussion of problems regarding the fire detection equipment, It was found that there were problems with the ship's lack of coordination with the company and the responsibility of the ship's officers for fire detection equipment that is lacking so that the fire detection device does not function properly. Therefore, the captain must ensure that safety equipment such as tools to start activities to achieve safety from fire hazards is also carried out to control reports made by officers responsible for this equipment. The results of the research and observation can be concluded that shipping companies pay less attention to safety for their crews including ships and their cargo because of a lack of concern for the procurement of safety equipment on board. The author’ is that it is hoped that the participation of shipping companies in supporting the procurement of ship safety equipment for safety at sea.